Civil War in South Sudan: Conflict Resolution through Mediation by the African Union - Gunawan, Yordan; Prameswari, Elfa Rheanna; Tsaabita , Dinysia Dzakiyya (Universitas Muhammadiyah Surakarta, 2024)
ABSTRACT Purpose of the study: This article discussed the historical scope of the Civil War in Sudan and outlined the causes of the Sudanese civil war conflict, which has not been resolved despite mediation efforts. Methodology:  The article provided the information objectively by conducting a literature review from reliable sources, such as national and international publications, and subdividing the content into comprehensive categories. Results: This article shows that the cause of the Civil War in Sudan was political complications and ethnic tensions, which caused each side to attack the other. The tensions that arise make it difficult to resolve conflicts due to the lack of commitment from each party to carry out the obligations that have been agreed upon as a result of mediation. Finally The ICC court decision number ICC-02/05-01/20-391 Decision on the designation of a Single Judge of Pre-Trial Chamber I was one step ahead on the processing the war crimes perpetrator Applications of this study: This research offers a thorough examination of the origins, progression, and settlement of violence in South Sudan. This analysis of the accomplishments and failures of the African Union’s mediation efforts in the South Sudan conflict can aid researchers and policymakers in better understanding this conflict and creating more practical measures for its resolution. List the various causes of war in South Sudan, including discrimination, economic disparity, and ethnic divisions. Using this knowledge, ways to deal with these issues and avert further conflict can be developed. The African Union’s mediation efforts in South Sudan’s conflicts are examined in this paper. By using this material, more people will be aware of the potential contributions regional organizations can make to the process of conflict resolution. Novelty/ Originality of this study: This research is the first to offer a thorough examination of the dynamics, causes, and settlement of violence in South Sudan. It had hitherto only addressed one facet of this conflict. It will examine the achievements and shortcomings of the African Union’s efforts to mediate the South Sudanese conflict. This analysis is significant because it can teach unites political, economic, and social ideas. It helps conflict mediators understand how regional groups might resolve issues. Courts may see the African Union's South Sudanese Civil War mediation differently. They'll likely see African Union mediation as a method to promote peace. Courts support international law-based mediation that involves all parties since South Sudan is independent and can decide its own future. Courts prioritize a peace settlement that addresses all sides' concerns, including civic society and the poor. They emphasize rigorous enforcement and execution procedures to support any solution, as well as international participation to maintain peace and stability in South Sudan. By using this knowledge, regional organizations can play a more effective role in other international disputes. Because of its uniqueness and novelty, this study can significantly advance our knowledge of the South Sudanese war and the ways in which regional organizations resolve disputes. Keywords: Civil War, Intergovernmental Authority on Development, Sudan